Avaliação da prevalência do bruxismo infantil e sua relação com o plano terminal dos segundos molares decíduos - Junqueira, Tatiana Helena (2009)
Bruxism is a parafunctional activity of the masticatory system that is characterized by teeth-clenching or grinding, with rhythmic muscular contractions, being more frequent during sleep. This research aimed at assessing the prevalence of bruxism in the deciduous teeth and verifies the association between this parafunctional habit with the terminal relationship of second deciduous molars. Therefore, 1.011 record cards from the documentation files of the City University of São Paulo, UNICID, from which 74 record cards were excluded because they did not meet the inclusion criteria. Therefore, 937 children of both sexes, in the age group between 2 to 6 years, from six EMEI located in Tatuapé neighborhood, eastern zone of São Paulo, constituted the sample of this study. The data were collected in the year of 2005 by means of questionnaires answered by the parents/guardians and clinical exams, performed in the school environment, to obtain the occlusal characteristics in the antero-posterior direction. The statistical tests, Student’s-t and Exact Fisher were used, with a 5% level of significance. In the view of the results, the prevalence of the parafunctional habit of bruxism was of 29.3% of the total sample and the prevalence with regard to the terminal relationship of the second deciduous molars was of 17.3% for the mesial degree, 10.5% for the distal degree and 72.3% for the straight terminal plane. With regard to the association of bruxism with the type of terminal relationship, significant results were not found. It was also verified that children who sleep restlessly presented 2.4 times more chances of having bruxism and the ones with headache, 1.6 times. It could be concluded, established in the results of this research, that the oclusal relationship in the anteroposterior direction does not present relation with the parafunctional habit of the bruxism.